Effect of Aerobic Exercise on Mental Health in Older Adults: A Meta-Analysis of Randomized Controlled Trials - Yao, Lei; Fang, Hanliu; Leng, Wanchun; Li, Junfeng; Chang, Jindong (Frontiers in Psychiatry, 2021)
Introduction: The recommendation of exercise programs in the senior population may benefit inactive and sedentary individuals and improve and help to treat specific health conditions. The purpose of this review is to summarize the published evidence from RCT studies of aerobic exercise interventions for mental health in older adults over the last 20 years. Methods: A literature search was conducted using electronic databases including Web of Science, PubMed/Medline, and ProQuest. Results: A total of 15 studies met the inclusion criteria. The subjects of these studies were aged 60 years or older and had various physical health statuses. In 15 studies, the mean effect size for the experimental outcome was 0.56 ± 0.39 (95%CI: 0.36–0.76). One-way ANOVA indicated no significant differences in the intervention duration [F(2,15) = 0.919, p = 0.420], subject category [F(2,15) = 0.046, p = 0.955], or measurement category [F(3,14) = 0.967, p = 0.436]. However, there were significant differences in exercise frequencies [F(2,15) = 6.03, p = 0.012]. Conclusion: The available evidence suggests that aerobic exercise is beneficial for improving the mental health of adults aged 60 years and older. The intervention effect can be achieved regardless of the type of subject and the duration of the intervention. Further, the present study indicates that low-frequency, long-term and regular aerobic exercise is more effective for older adults. Therefore, we recommend that older adults to exercise at a low frequency depending on their physical condition.